A Study on the Generation Mechanism and Development Process of Piping Based on the Theory of Muddy Water Seepage. (30th July 2022) - Gao, Jun; Dang, Jiaote; Han, Xiaoke; Fang, Jianyin; Ren, Jie; Tian, Wei
Abstract : In the process of piping development, the sediment carried by seepage causes the change of porosity and then causes the change of permeability coefficient. Therefore, piping belongs to muddy water seepage (i.e., unstable seepage). Based on the theory of muddy water seepage, the new control equation of piping model is established. The generation mechanism and development process of piping for white fine sand and sand gravel are explored. The advantages for the new control equation of piping model are discussed. The results show that the new control equation of piping model is not only simpler in form but also easier to solve and can better describe the characteristics of piping generation, development, and stability. Compared with white fine sand (the initial relative density and porosity are smaller, and the initial permeability coefficient and critical gradient are larger), the porosity, permeability coefficient, seepage flow, and sediment volume of sandy gravel increase faster with time. When the porosity is the same, the permeability coefficient, seepage flow, and sediment volume of sand gravel are larger. The smaller the area affected by piping, the faster the increase of porosity, permeability coefficient, seepage flow, and sediment volume. When the porosity and permeability coefficient are the same, the seepage flow and sediment volume are smaller. The smaller the initial porosity and permeability coefficient, the later the generation, and development of piping. It can provide a reference for piping danger forecast and emergency response.